Depression according to social assistance in institutionalized and non-institutionalized older adults in Ciudad Juárez, México. - Trejo Villalobos, Jessica Abigail (2023)
Currently, the increase in depression rates in older adults, in the second most frequent mental disorder at the border. The symptoms of this disorder go unnoticed and are consistent with other problems experienced by older adults. With the objective of identifying the level of depression in older adults in the stays as in the neighborhoods of ciudad Juárez according to the social assistance received. The present study is of quantitative type, with comparative descriptive scope. The instrument used was the Scale of Geriatric Depression-Yesavage Test questionnaire. The sample consisted of 58 older adults, being the non-probabilistic sampling technique for convenience. As a result, the depression in the sample of older adults from stays and colonies in Ciudad Juárez was a statistically significant difference according to social assistance. Reporting, that older adults without studies obtained a higher degree of depression. It is shown that institutionalized older adults who do not receive social assistance have a higher degree of depression. It is evident that more than half of the sample of older adults in ciudad Juárez, the depressive state was in a normal range. Therefore, it is concluded that the normal level of depression was higher in older adults than in the neighborhoods of ciudad Juárez without social assistance. In addition, schooling influences the depression of older adults, since those who do not have studies have a greater depressive state in the change to those with a level of professional schooling.